Marker-trait association and epistasis for brown rust resistance in sugarcane - Santos, Fernanda R. C.; Pinto, Luciana R.; Carlini-Garcia, Luciana A.; Gazaffi, Rodrigo; Mancini, Melina C.; Gonçalves, Bruna S. [UNESP]; Medeiros, Cibele N. F. [UNESP]; Perecin, Dilermando [UNESP]; Garcia, Antonio A. F.; Souza, Anete P.; Zucchi, Maria I. (Springer, 2015)
Sugarcane brown rust, caused by Puccinia melanocephala, is one of the major sugarcane diseases. The detection of molecular markers associated to brown rust resistance and also of its epistatic interactions were investigated in a mapping population obtained by crossing the brown rust susceptible clone IACSP953018 and the resistant cultivar IACSP933046. Resistance was evaluated in a field trial in plant cane and first ratoon under natural infection and scored using a diagrammatic scale from 1 (most resistance) to 9 (most susceptible). A total of 488 single dose markers (amplified fragment length polymorphism AFLP, genomic microsatellite gSSR and expressed sequence tag derived microsatellites EST-SSRs) were evaluated through a single marker trait association approach for brown rust resistance. Sixty one putative quantitative trait alleles (QTA) for brown rust (30 in plant cane, 31 in ratoon cane; 10 of them was common for both crop years) were detected of which several were related to resistance. Twenty one (34 %) of the markers associated to QTA derived from ESTs. Some of them have similarity to genes/proteins related to disease response pathways. The estimates of the proportion of the total phenotypic variation () explained by each significant main QTA effect ranged from 1.84 to 7.22 %, while the total explained variance estimates were 37.25 % (plant cane) and 43.26 % (ratoon cane) considering all main significant QTA effects. Fifty significant digenic epistatic interactions were suggested with the majority (68 %) contributing to increase brown rust resistance. Together, these probable epistatic effects explain 16.26 % (plant cane) and 17.22 % (ratoon cane) of the total phenotypic variance. Although evidence of epistasis was observed, linkage cannot be ruled out as the majority of the markers involved in the digenic interaction could not be addressed to any linkage group. The results suggest that epistasis may have an important contribution on sugarcane resistance to brown rust.
Keywords: EST-SSR; Puccinia melanocephala; Quantitative trait loci-QTL; Saccharum spp.